Traumatic abdominal wall hernia with evisceration secondary to handlebar injury - T.N.Diem Vu; Denise B. Klinkner (Journal of Pediatric Surgery Case Reports, 2019)
We report the case of a 10 year-old male who presented to an outside hospital after falling onto a bicycle handlebar. The patient removed the handlebar embedded in his abdomen and noted bowel protruding from the wound. Upon presentation to the outside facility, he was hemodynamically stable and underwent whole-body CT scan. This demonstrated no hollow viscus, biliary, or vascular injuries. The patient was transferred to our institution where he was brought to the operating room. He underwent exploration, reduction of bowel, and closure of the abdominal hernia. We present a rare case of abdominal evisceration with traumatic hernia secondary to handlebar injury. Our aim with this report is to emphasize the importance of early surgical treatment of this rare phenomenon and to review the relevant literature. Keywords: Traumatic hernia, Hernia, Handlebar injury